"رواج نامۂ سوات" میں موجود مویشیوں کی زکوۃ کے متعلق والئی سوات کے قوانین کا شرعی و تحقیقی جائزہ (Al-Qamar, 2023)
Zakāt is a financial liability imposed by Sharī’ah (Islamic law) on believers. The legality of such obligation, of course, is derived from several verses of the Holy Qurān and Ḥadīth of the Holy Prophet (SM). Such obligation, in terms of its substance, can be divided, mainly, in currencies and animals.  The latter kind, being a complex one, has been elaborated by Islamic law with minute details. Additionally, head of the state has the responsibility to make necessary arrangements for the management of such financial obligation- ranging from the collection to the division.  Wālī Swat (a famous ruler of Swat), being a head of the Swat State, fulfilled this responsibility in the best possible way. At his time, a very unique system was introduced for the collection of Zakāt (from those individual having Nisāb for the same). The contemporary Sharī’ah scholars have a difference of opinion whether such mechanism, introduced for the collection of Zakat, was entirely based on Sharī’ah or not. The present work, following this question, aims to find out the best possible answer to it.  While doing so, all verdicts, related to the issue under consideration, have been analyzed for the perspective of Islamic law. The work of the classical Muslim jurists (fuqahā) has been citied extensively; while analyzing a verdict. The Hanfī school of thought, however, has been offered more comparatively to other school of thought- owing to the fact that the legal system, prevailing in the regime of Wālī Swat, was, predominantly, based on the principles of the same school. Further, content analysis technique, a kind of qualitative research has been adopted for the investigation of the issue.
Keywords: Wālī Swat; Zakāt; Legal Verdicts; Islamic Law; Financial Obligation; Hukam Namā; Sharī’ah; fuqahā